Development of patient satisfaction questionnaires: I. Methodological issues. Issue 3 (September 1992) - Bamford, C; Jacoby, A
Abstract : OBJECTIVES--To develop a method for conducting postal surveys of patients' views and experiences of general practitioner care and to produce an off the shelf tool for general practice audit. DESIGN--Prospective study of performance of two patient questionnaires assessing accessibility to services (questionnaire 1) and interpersonal aspects of care (questionnaire 2) in comparing general practices. SETTING--Five general practices in Newcastle upon Tyne. PATIENTS--3800 patients aged 16 and over, 1900 randomly drawn from family health services authority lists for each practice (questionnaire 1) and 1900 drawn from practice records (questionnaire 2). MAIN MEASURES--Response rates and technical evaluation of performance of the questionnaires (reliability, item nonresponse, ineligible response, sensitivity, and validity). RESULTS--Response rate for questionnaire 1 was 77% (range 69% to 83%) and to questionnaire 2, 82% (77% to 86%). Analysis of respondents and nonrespondents showed that significantly more women, people aged 65 or more, and those consulting in the past six months returned the questionnaires. Technical evaluation indicated good face validity and content validity and good internal consistency. CONCLUSIONS--A standardised off the shelf tool for audit was developed, and it will be a valuable model for future audits in general practice.